1992
DOI: 10.1056/nejm199210153271606
|View full text |Cite
|
Sign up to set email alerts
|

The Publication of Sponsored Symposiums in Medical Journals

Abstract: Symposiums sponsored by drug companies often have promotional attributes and are not peer-reviewed. Financial relations among symposium participants, sponsors, and journals should be completely disclosed, symposiums should be clearly identified, and journal editors should maintain editorial control over contributions from symposiums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(58 citation statements)
references
References 20 publications
2
53
0
3
Order By: Relevance
“…21 For-profit organizations also are more likely to support favorable review articles, journal supplements, and promotional materials on an "author-for-hire" basis. 22,23 Finally, it has been shown that Table 3. Total Number of Citations per Publication According to Funding Source Stratified by Potential Confounders financial relationships between industry and scientific investigators are associated with an increased likelihood of a pro-industry conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…21 For-profit organizations also are more likely to support favorable review articles, journal supplements, and promotional materials on an "author-for-hire" basis. 22,23 Finally, it has been shown that Table 3. Total Number of Citations per Publication According to Funding Source Stratified by Potential Confounders financial relationships between industry and scientific investigators are associated with an increased likelihood of a pro-industry conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…29,30 Our access to the extensive libraries and interlibrary loan requests may not be representative of a typical clinician's access, and our repeated efforts to obtain documents may be greater than those of a practising clinician. Finally, some unconfirmed references may have been due to errors in the citation listing in the ad.…”
Section: Discussionmentioning
confidence: 99%
“…He continued, more pointedly, that "as editors we delight in the revenue from their adventures in competitive advertising, even as we seek to put restraints on its ultrapersuasiveness and keep it within the bounds that medical propriety and a sense of service to humanity have set." Yet constant vigilance has been required to maintain firewalls between promotion and education (1992).…”
Section: Challenges Then and Nowmentioning
confidence: 99%